A successful case of maturogenesis by stepwise excavation using calcium-enriched mixture cement - Saeed Asgary; Laleh Alim Marvasti (Exploration of Medicine, 2023)
This case report demonstrates the successful induction of apexogenesis in an extensively carious lower right first molar with immature roots through the use of stepwise excavation and calcium-enriched mixture (CEM) cement as an indirect pulp capping material. The patient, an 8-year-old boy, presented with pain and carious pulp exposure. The initial treatment involved removing soft dentin and applying CEM cement as an indirect pulp cap. The patient experienced pain relief after 24 h, and subsequent follow-up appointments showed complete healing and maturation of the tooth. The case highlights the potential of indirect pulp treatment with CEM cement and emphasizes the importance of regenerative biomaterials in promoting healing and dentin bridge formation. Further clinical work and research are recommended to explore the efficacy of this treatment approach.